2011
DOI: 10.1007/s10930-011-9358-5
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Enzymatic Study of Rice BADH Wild-Type and Mutants: An Insight into Fragrance in Rice

Abstract: Betaine aldehyde dehydrogenase 2 (BADH2) is believed to be involved in the accumulation of 2-acetyl-1-pyrroline (2AP), one of the major aromatic compounds in fragrant rice. The enzyme can oxidize ω-aminoaldehydes to the corresponding ω-amino acids. This study was carried out to investigate the function of wild-type BADHs and four BADH2 mutants: BADH2_Y420, containing a Y420 insertion similar to BADH2.8 in Myanmar fragrance rice, BADH2_C294A, BADH2_E260A and BADH2_N162A, consisting of a single catalytic-residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…But the 3 bp insertion was present at a much higher frequency in our sample. It was recently demonstrated that this insertion did not modify the gene expression but the addition of a tyrosine to the peptide interfered with cofactor NAD + binding, lowered enzyme activity and led to accumulation of acetyl-pyrroline, although at a lower level than in accessions carrying the 8 bp deletion ( [Vanavichit and Yoshihashi 2010], [Wongpanya et al 2011], [Myint et al 2012]). We found one additional deletion of 43 bp at the very end of the gene in 22 accessions that was specific to Myanmar accessions.…”
Section: Discussionmentioning
confidence: 99%
“…But the 3 bp insertion was present at a much higher frequency in our sample. It was recently demonstrated that this insertion did not modify the gene expression but the addition of a tyrosine to the peptide interfered with cofactor NAD + binding, lowered enzyme activity and led to accumulation of acetyl-pyrroline, although at a lower level than in accessions carrying the 8 bp deletion ( [Vanavichit and Yoshihashi 2010], [Wongpanya et al 2011], [Myint et al 2012]). We found one additional deletion of 43 bp at the very end of the gene in 22 accessions that was specific to Myanmar accessions.…”
Section: Discussionmentioning
confidence: 99%
“…The crystallization of the 503-amino acid Os2AP protein from the non-aromatic isogenic line was reported (Kuaprasert et al 2011 ). The structure was predicted to contain three binding domains: an NAD+ binding, an oligomerization, and a substrate binding domain where an aldehyde dehydrogenase cysteine subdomain was located (Chen et al 2008 ; Wongpanya et al 2011 ). In the aromatic isogenic lines and KDML105, the specific 8-bp deletion was identified within exon 7 of the AMADH of KDML105, causing a premature stop codon, non-sense-mediated decay, and non-functioning of Os2AP , respectively (Vanavichit et al 2005 ).…”
Section: Cooking Quality Fragrance and Interaction With Environmentmentioning
confidence: 99%
“…In aromatic coconut, a base substitution was identified, which resulted in an amino acid change from alanine to proline at position 442 near the C-terminal of the protein. This might result in the fragrant phenotype in coconut, because this amino acid change was located within the substrate binding domain of the enzyme Wongpanya et al, 2011). Proline contains a side chain with a ring structure that may affect the overall structure of this domain of the enzyme (Figure 3), resulting in instability and a non-functional enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…However, in rice, biosynthesis of this aromatic compound results from the metabolism of 4-aminobutyraldehyde (AB-ald) to 1-pyrroline, which is then converted to 2AP due to the lack of the functional enzyme, betaine aldehyde dehydrogenase homologue 2 (BADH2) (Yoshihashi et al, 2002;Vanavichit et al, 2005).…”
Section: Introductionmentioning
confidence: 99%